Improving the efficiency of secondary load frequency control in a power system considering internal tie-line power exchanges - Yandulskiy, Oleksandr; Hulyi, Volodymyr; Nesterko, Artem; Kovalenko, Mykhailo; Tymokhin, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2025)
This study's object is the processes of frequency and power adjustment in the power system of Ukraine, which is connected to parallel operation with a neighboring power system. The current issues related to increasing the efficiency of secondary frequency and power adjustment in the unified power system of Ukraine, which operates in parallel with the European power system (ENTSO-E), have been considered. The factors associated with the introduction of renewable energy sources, the growing role of decentralized generation, and the need to take into account the limitations of internal tie-lines in the power system when distributing the load have been analyzed. An analysis of approaches to automatic frequency and power adjustment was conducted; the shortcomings of existing solutions were identified, including simplification of the network topology, failure to take into account the technical limitations of power units and reserves, as well as limitations in internal controlled tie-lines. An improved approach to secondary adjustment based on the method of predictive models has been proposed, which makes it possible to take into account these limitations and improve the efficiency of secondary frequency and power adjustment in the power system. The study of the processes was performed on a dynamic model of the power system with real parameters; the effectiveness of the proposed approach was confirmed by comparison with the conventional proportional-integral control law of the automatic frequency and power control system. It has been shown that the implementation of the devised approach provides a reduction in frequency recovery time by 8% and prevents overloading of controlled sections, increasing the stability and reliability of the power system under the conditions of modern challenges. The has proposed approach made it possible to increase the efficiency of secondary frequency and power control in the power system